Czech-Taiwan Relations: a Turn to the East? - Mikhail V. Vedernikov (Современная Европа)
The article examines the dynamics of Czech-Taiwan relations at the present stage. Since the early 1990s. Prague began to pay close attention to a partially recognised state in its foreign policy. The interest was caused by the special status of the island and the similarity of its position, according to President V. Havel, with socialist Czechoslovakia. The key periods in the history of relations between Prague and Taipei are outlined: the phases of active interaction were replaced by stages of decreasing cooperation. It is emphasised that since 2022, after the liberal-democratic coalition came to power, the Taiwanese track of Czech diplomacy has become its core direction. Czech politicians revived Havel's value policy, but abandoned the personal factor in advancing the agenda, focusing on a whole-government approach.